People Equity And The Learning And Growth Of The Management Of Local Traditional Medicine - Shabudin, Siti Khalijah (2007)
The purpose of this research is to investigate the present relationship between people equity and the learning and growth of the management of the local traditional medicine firms. It is also to determine the level of people equity for the group under study. One hundred and sixty sets of questionnaires were mailed to the management of eighty of the firms of local traditional medicine in Malaysia with 50% response rate. The predictors for the learning and growth (core elements of people equity) are capabilities, job alignment and employee engagement, while for the dimension of learning and growth, access to strategic information, employee satisfaction on superior executive leadership, organization structured for continuous improvement and employee satisfaction on quality work environment are being studied.